2011
DOI: 10.1039/c1ib00128k
|View full text |Cite
|
Sign up to set email alerts
|

Migration dynamics of breast cancer cells in a tunable 3D interstitial flow chamber

Abstract: The migration of cells such as leukocytes, tumor cells, and fibroblasts through 3D matrices is critical for regulating homeostasis and immunity and for driving pathogenesis. Interstitial flow through the extracellular matrix, which can substantially increase during inflammation and in the tumor microenvironment, can influence cell migration in multiple ways. Leukocytes and tumor cells are heterogeneous in their migration responses to flow, yet most 3D migration studies use endpoint measurements representing av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(188 citation statements)
references
References 43 publications
4
180
1
Order By: Relevance
“…Data of Haessler et al revealed that interstitial flow increases the percentage of cells that become migratory as well as increases the migrational speed in about 20% of the cells 42 . In addition to study the chemotactic behavior of cells, e.g., leukocytes/lymphocytes or tumor cells, a 3D microfluidic setting is also a suitable tool to study tumor cell intravasation and endothelial barrier function 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Data of Haessler et al revealed that interstitial flow increases the percentage of cells that become migratory as well as increases the migrational speed in about 20% of the cells 42 . In addition to study the chemotactic behavior of cells, e.g., leukocytes/lymphocytes or tumor cells, a 3D microfluidic setting is also a suitable tool to study tumor cell intravasation and endothelial barrier function 43 .…”
Section: Discussionmentioning
confidence: 99%
“…IF has been shown to induce rheotaxis when cells are seeded at sufficiently high density for paracrine chemokine fields to interfere with autocrine chemokine fields (17), and cells migrating upstream have been shown to migrate with increased persistence (35). We seeded cells at a density shown to induce preferential upstream migration of MDA-MB 231 (6 × 10 5 cells per mL) and applied 4.6 ÎŒm/s flow for 8 h, tracking the cells by taking images every 15 min.…”
Section: Paxillin Is Required For Upstream Actin Polarization and Promentioning
confidence: 99%
“…It has also been observed, at relatively lower cell densities, that tumor cells migrate in the direction of the flow. Haessler et al (2011) reported that an increase in interstitial flow was found in the microenvironment within a tumor mass and that the flow influenced tumor cell migration. In particular, autologous chemotaxis, a directed cell migration induced by interstitial flow, has been identified as a potentially important mechanism; in this case, cancer cells migrate in the direction of the flow (Shieh and Swartz 2011;Fleury et al 2006;Shields et al 2007).…”
Section: Effect Of Interstitial Flow On Hcc Cellsmentioning
confidence: 99%
“…Particularly, interstitial flow, the convective transport of fluid through tissue ECM, has been demonstrated to affect the morphology and migration of various cell types including endothelial cells and tumor cells (Haessler et al 2011). It is also known that interstitial flow is related to the metastasis of tumors and the guidance of tumor cell movement (Shieh and Swartz 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation